2019
DOI: 10.30802/aalas-cm-19-000029
|View full text |Cite
|
Sign up to set email alerts
|

Interacting Influences of Sleep, Pain, and Analgesic Medications on Sleep Studies in Rodents

Abstract: This overview provides a brief summary of the complex interactions that link sleep, pain, and analgesic medications. Sleep scientists and clinicians are well aware of these relationships and understand that maintaining healthy pain-free subjects in a stable environment is essential to generating interpretable data and valid conclusions. However, these concepts and the data that support bidirectional interactions between sleep and pain may be less known to those who are not sleep scientists yet need such infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…65 Research has consistently demonstrated that pain and sleep problems are related. 7 Based on both human and animal studies, a bidirectional relationship has been proposed, 2,50,80,85,87 with more recent longitudinal and microlongitudinal studies (primarily) indicating a stronger influence of sleep problems on pain than vice versa. 3,7,9,20,25,38,83 Still, many questions remain regarding the relationship's underlying mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…65 Research has consistently demonstrated that pain and sleep problems are related. 7 Based on both human and animal studies, a bidirectional relationship has been proposed, 2,50,80,85,87 with more recent longitudinal and microlongitudinal studies (primarily) indicating a stronger influence of sleep problems on pain than vice versa. 3,7,9,20,25,38,83 Still, many questions remain regarding the relationship's underlying mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Diseases associated with ageing and cognitive dysfunction of humans naturally occur in dogs across the lifespan in a similar manner 27 ; the progression of age-related cognitive decline and comorbidities offers study of environmental, dietary, and longitudinal effects, unlike induced rodent models where changes occur over a brief time course 2,3,28,30 . Researchers have noted sleep disturbances as a result of ageing, cognitive dysfunction, and chronic pain for humans and dogs [31][32][33][34][35][36][37] . Takeuchi and Harada 37 concluded that sleep pattern changes, such as decreased nighttime sleep efficiency, are a result of ageing in laboratory-housed dogs, comparable to humans.…”
mentioning
confidence: 99%
“…Takeuchi and Harada 37 concluded that sleep pattern changes, such as decreased nighttime sleep efficiency, are a result of ageing in laboratory-housed dogs, comparable to humans. It has also been established that sleep and pain hold a bidirectional relationship, in which sleep disturbance may be a result of sleep deficiency enhancing pain or the presence of pain disturbing sleep [31][32][33]38 . Knazovicky et al 34 examined nighttime activity of companion dogs with osteoarthritis under blinded treatment and placebo conditions; using an owner questionnaire, they found that chronic pain impacts quality of sleep contributing to sleep disturbance.…”
mentioning
confidence: 99%
“…Patients with comorbid chronic pain and sleep disturbances have greater severity and longer duration of both symptoms. Since some medications are only effective for one symptom 11,72 , pharmacological Fig. 3 | NAc ensemble formed in inflammatory pain.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with comorbid chronic pain and sleep disturbances have greater severity and longer duration of both symptoms. Since some medications are only effective for one symptom 11 , 72 , pharmacological options for the comorbidity between chronic pain and sleep disturbance remain limited. Our current findings set the NAc ensemble as an interplay regulating both sleep and pain-like behaviors, raising the possibility of developing NAc-centered treatments, such as deep brain stimulation or transcranial magnetic stimulation 73 – 77 .…”
Section: Discussionmentioning
confidence: 99%